2018
DOI: 10.1007/s00540-018-2492-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative renal function in parturients with severe preeclampsia who underwent cesarean delivery: a retrospective observational study

Abstract: Although postoperative renal dysfunction is relatively rare after cesarean delivery, preeclampsia is considered as the high-risk population. On the other hand, hydroxyethyl starch (HES) administration for preventing maternal hypotension induced by spinal anesthesia for cesarean delivery is a common practice. However, the effect of HES administration during cesarean delivery on postoperative kidney function in parturients with severe preeclampsia is not well investigated. We retrospectively reviewed both medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Studies have shown that a prior surgical cesarean section leads to an increase to the progression of preeclampsia in a subsequent pregnancy. The extended interval between pregnancies among patients who previously experienced cesarean section is a major risk factor for preeclampsia [ 30 , 31 ], suggesting that the advantage of a high parity regarding the risk of preeclampsia is only transient. This evidence supports the considerably high and increasing cesarean section rate in West Bengal in India [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a prior surgical cesarean section leads to an increase to the progression of preeclampsia in a subsequent pregnancy. The extended interval between pregnancies among patients who previously experienced cesarean section is a major risk factor for preeclampsia [ 30 , 31 ], suggesting that the advantage of a high parity regarding the risk of preeclampsia is only transient. This evidence supports the considerably high and increasing cesarean section rate in West Bengal in India [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Huang C et al [ 47 ], the incidence of AKI in patients with SP who underwent caesarean section was as high as 60%. The clinical situation of the patient, the heterogeneity for AKI definition used by the authors and the intraoperative management of blood volume can decisively influence the incidence of AKI associated with caesarean section [ 49 , 50 , 51 ]. In our series, we relate caesarean section to the association between AKI in the SP patients however, since we did not record the time at which AKI appears in patients, before or after cesarean section, we cannot attribute a causal association of it to the development of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of AKI associated with preeclampsia is relatively good as long as there are no other associated complications, such as sepsis, DIC or severe bleeding, and most patients resume normal renal function postpartum [ 29 , 50 ]. Persistent renal dysfunction and the need for dialysis is more common in patients with previous CKD [ 20 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the study by Mazda et al [1] regarding postoperative acute kidney injury (AKI) in parturients with severe preeclamsia. We would like to discuss the clinical implication of the study.…”
mentioning
confidence: 99%